The Relationship Between Anxiety and Performance: A Behavioral Perspective - Humara, M. (Athletic Insight - The Online Journal of Sport Psychology, 1999)
This paper examines the relationship between anxiety and performance from a cognitive-behavioral perspective. Previous research in the field has suggested that the majority of consultations conducted by sport psychologists are related to anxiety. Included is a discussion on the theoretical underpinnings of anxiety and how it relates to performance. Research conducted on the relationship between anxiety and performance is also discussed. A review of the cognitive-behavioral treatments that have been used for anxiety reduction and performance enhancement within the field of athletics is included. Suggestions for future research and practical considerations are listed in the conclusion.